Stages of development of graphic posters - Chernysh, Maksim; Zhytienova, Natalya (Professional Art Education, 2024)
Object. Characterize the stages of development of graphic posters, determine the main tasks and goals at each stage of their development. In accordance with the set goal, the following tasks were allocated: Analyze scientific sources of information in accordance with the defined topic of the article; Highlight the features of creating a graphic poster and consider their types; Characterize the stages of development of graphic posters with the definition of goals and objectives at each stage. Material. The historical impact on the development of graphic posters has been considered and evaluated. It has been established that there is a lot of graphic products on the design market, which is progressing and developing at a rapid pace, however not all graphic products are of good quality. However, it has been found that the development of a graphic poster requires a sufficiently thorough approach to its design. The article discusses the stages of development of graphic posters, with the definition of goals and objectives at each stage of development, namely: Defining the goals and objectives of the poster; Analysis of the target audience; Gathering; Developing a concept; Creating sketches; Designing a layout; Reviewing; Printing and placement. Result. We have identified the following stages of developing graphic posters: defining the goals and objectives of the poster. The purpose of this stage is to identify the goal of the poster, i.e. what information needs to be conveyed to the audience and what feedback is desired from the audience after viewing the poster. The task of this stage is to determine the type of poster being developed. Analyzing the target audience. The purpose of this stage is to determine the audience for which the poster is being developed. Gathering ideas. The purpose of this stage is to generate ideas. The task is to develop a mood board. Developing the concept. The purpose of this stage is to create the concept of the poster. The task is to finalize the overall style, color palette, typographic elements, selection of images, and design of compositional solutions. Creating sketches. The purpose of this stage is to develop sketches of the future poster, which involve quick sketches and help to implement the desired concept into the poster design. The task is to develop sketches that can be created both on ordinary paper and using graphic programs or online services. Designing the layout. The purpose of the sixth stage is to design the layout of the poster. The task is to design the layout of the poster, which reflects how it will look and includes all of its necessary elements. Reviewing. The purpose of this stage is to review the developed layout of the poster. The task is to obtain feedback from the audience to identify design flaws and improve it. This can be done by demonstrating the poster to colleagues or friends, posting it on social media, etc. Printing and placement. The purpose is to print and place the poster. The task is to finalize the design of the poster, based on the identified flaws, and print and place it. For example, if a promotional poster is created, it can be placed in places where potential customers can see it. If a social or environmental poster is created, it can be placed in places where people interested in this topic can see it. Conclusions. The types of graphic posters were analyzed, which include social, authorial, mass, political, informational-instructional, educational-instructional, and environmental. The stages of development of graphic posters were characterized, which include: definition of the goals and objectives of the poster, analysis of the target audience, gathering of ideas, development of the concept, creation of sketches, design of the layout, reviewing, printing, and placement. The purpose and objectives were defined at each stage of development. It is generally accepted that graphic posters can effectively communicate the necessary information and meaning to the audience. However, the quality development of graphic posters requires taking into account many aspects. In our opinion, promising directions for further research are to define the requirements for disclosing the specifics of the design of graphic posters.